Sustainable Taxi Fleet: An Approach to the Contribution of Green Taxation - Dinis, Ana (2023)
It is a well-known fact that the automotive sector plays a key role in a country’s socio-economic de- velopment, due to the large contribution of vehicles to greenhouse gas emissions (GHG). Alternatives such as car-sharing, public transport, cycling, the transition to electric vehicles, or walking can help reduce emissions. Therefore, it becomes a sector where environmental regulation should be demanded. This research aims to contribute to the tax literature by extending previous studies on corporate taxa- tion by evaluating green tax incentives as an effective environmental tax measure. Considering taxis as an important part of urban public transport systems, the authors set out to investigate Portuguese taxi companies that have taken advantage of tax incentives for less environmentally polluting vehicles. The authors conclude that the income tax level, the economic profit, and the number of employees, are determining factors in these firms ‘access to the tax incentives under study.